Identification of (4-(9H-fluoren-9-yl) piperazin-1-yl) methanone derivatives as falcipain 2 inhibitors active against Plasmodium falciparum cultures - Hernández-González, Jorge E. [UNESP]; Salas-Sarduy, Emir; Hernández Ramírez, Luisa F.; Pascual, María J.; Álvarez, Diego E.; Pabón, Adriana; Leite, Vitor B.P. [UNESP]; Pascutti, Pedro G.; Valiente, Pedro A. (Elsevier, 2018)
Background: Falcipain 2 (FP-2) is the hemoglobin-degrading cysteine protease of Plasmodium falciparum most extensively targeted to develop novel antimalarials. However, no commercial antimalarial drugs based on FP-2 inhibition are available yet due to the low selectivity of most FP-2 inhibitors against the human cysteine proteases. Methods: A structure-based virtual screening (SVBS) using Maybridge HitFinder™ compound database was conducted to identify potential FP-2 inhibitors. In vitro enzymatic and cell-growth inhibition assays were performed for the top-scoring compounds. Docking, molecular dynamics (MD) simulations and free energy calculations were employed to study the interaction of the best hits with FP-2 and other related enzymes. Results and conclusions: Two hits based on 4-(9H-fluoren-9-yl) piperazin-1-yl) methanone scaffold, HTS07940 and HTS08262, were identified as inhibitors of FP-2 (half-maximal inhibitory concentration (IC50) = 64 μM and 14.7 μM, respectively) without a detectable inhibition against the human off-target cathepsin K (hCatK). HTS07940 and HTS08262 inhibited the growth of the multidrug-resistant P. falciparum strain FCR3 in culture (half-maximal inhibitory concentrations (IC50) = 2.91 μM and 34 μM, respectively) and exhibited only moderate cytotoxicity against HeLa cells (Half-maximal cytotoxic concentration (CC50) = 133 μM and 350 μM, respectively). Free energy calculations reproduced the experimental affinities of the hits for FP-2 and explained the selectivity with respect to hCatK. General significance: To the best of our knowledge, HTS07940 stands among the most selective FP-2 inhibitors identified by SBVS reported so far, displaying moderate antiplasmodial activity and low cytotoxicity against human cells. Hence, this compound constitutes a promising lead for the design of more potent and selective FP-2 inhibitors.
Keywords: Binding mode; Falcipain 2; Inhibition assay; Molecular dynamics; Plasmodium falciparum; Virtual screening